Knowledge construction around hybrid photovoltaic systems through Literature Based Discovery - Coral, Marco (2020)
Given the need to deepen the dynamics in the generation of new knowledge, with respect to renewable energies, in particular around hybrid photovoltaic systems, this study analyzes the research developed, through the “Literature Based Discovery” - LBD. A research chain is developed to capture emerging and other innovative or exploratory aspects. The steps followed have as a priority to generate the extraction and automated search, from the key- words, to group the results looking for their references, in addition to locating research on these semantic terms, concepts and the relationship between them through text mining. The results generate a grouping of topics based on the keywords, which were linked by LBD, these identify dependencies between various analyzes, concluding that LBD techniques generate correlations that are not explicitly seen, so it is necessary to carry out additional analyzes by the expert to correctly determine the implicit knowledge.